Nitrate Supply Routes and Impact of Internal Cycling in the North Atlantic Ocean Inferred From Nitrate Isotopic Composition. Issue 4 (19th April 2021) - Deman, F.; Fonseca‐Batista, D.; Roukaerts, A.; García‐Ibáñez, M. I.; Le Roy, E.; Thilakarathne, E. P. D. N.; Elskens, M.; Dehairs, F.; Fripiat, F.
Abstract: In this study we report full‐depth water column profiles for nitrogen and oxygen isotopic composition (δ 15 N and δ 18 O) of nitrate (NO3 − ) during the GEOTRACES GA01 cruise (2014). This transect intersects the double gyre system of the subtropical and subpolar regions of the North Atlantic separated by a strong transition zone, the North Atlantic Current. The distribution of NO3 − δ 15 N and δ 18 O shows that assimilation by phytoplankton is the main process controlling the NO3 − isotopic composition in the upper 150 m, with values increasing in a NO3 − δ 18 O versus δ 15 N space along a line with a slope of one toward the surface. In the subpolar gyre, a single relationship between the degree of NO3 − consumption and residual NO3 − δ 15 N supports the view that NO3 − is supplied via Ekman upwelling and deep winter convection, and progressively consumed during the Ekman transport of surface water southward. The co‐occurrence of partial NO3 − assimilation and nitrification in the deep mixed layer of the subpolar gyre elevates subsurface NO3 − δ 18 O in comparison to deep oceanic values. This signal propagates through isopycnal exchanges to greater depths at lower latitudes. With recirculation in the subtropical gyre, cycles of quantitative consumption‐nitrification progressively decrease subsurface NO3 − δ 18 O toward the δ 18 O of regenerated NO3 − . The low NO3 − δ 15 N observed south of the Subarctic Front is mostly explained by N2 fixation, although a contribution from the Mediterranean outflow is required to explain the lower NO3 − δ 15 N signal observed between 600 and 1500 m depth close to the Iberian margin. Key Points: Nitrate assimilation controls the nitrate isotopic composition in surface waters of the North Atlantic subpolar gyre Nitrate isotopic composition reveals that nitrate is supplied from subpolar to subtropical gyre by Ekman transport and isopycnal mixing N2 fixation and Mediterranean outflow have an impact on nitrate isotopic composition in the North Atlantic Ocean